Sams teach yourself Cobol in 24 hours - Hubbell, Thane (Sams teach yourself in 24 hours series., 1999)
Sams Teach Yourself COBOL in 24 Hours teaches the basics of COBOL programming in 24 step-by-step lessons. Each lesson builds on the previous one providing a solid foundation in COBOL programming concepts and techniques. Coupled with the source code and the compiler available from Fujitsu, this hands-on guide is the easiest, fastest way to begin creating standard COBOL compliant code. Business professionals and programmers from other languages will find this hands-on, task-oriented tutorial extremely useful for learning the essential features and concepts of COBOL programming. Writing a program can be a complex task. Concentrating on one development tool guides you to good results every time. There will be no programs that will not compile!